Harnessing GABA Pathways to Improve Plant Resilience Against Salt Stress - Jameel Mohammed Al-Khayri; Mohamed Abdel-Haleem; Emad Hamdy Khedr (Horticulturae)
Salinity has emerged as a critical abiotic stress factor, significantly limiting the growth, productivity, and quality of many crop species. As the global salinization of agricultural land continues to intensify, it is crucial to explore effective mitigation strategies to sustain crop yields. γ-Aminobutyric acid (GABA), a non-protein amino acid, is present in a variety of organisms, including plants, where it fulfills diverse roles under both optimal and stress conditions. In plants, GABA is intricately involved in nitrogen metabolism, amino acid biosynthesis, and the regulation of primary and secondary metabolic pathways. Functioning through the GABA shunt, it provides the carbon skeletons and energy required for biosynthetic processes and is vital for the regulation of carbon and nitrogen balance. Under abiotic stress conditions, particularly salinity, GABA rapidly accumulates, facilitating several protective mechanisms that help plants cope with stress. These include enhancing osmotic adjustment through the accumulation of osmolytes, protecting cellular structures such as chloroplasts, and improving chlorophyll fluorescence and photosynthetic efficiency. Moreover, GABA has been shown to boost antioxidant enzyme activity, reducing oxidative stress and mitigating the damage caused by reactive oxygen species (ROS) under salinity conditions. This study explores the multifaceted role of GABA in plants under saline environments, with a focus on its physiological, biochemical, and molecular mechanisms in enhancing plant resilience. By elucidating these mechanisms, we aim to highlight the potential of GABA as a natural biostimulant to improve crop performance and sustainability in saline soils.